Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.